2004
DOI: 10.1590/s0066-782x2004000300005
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre evolução da função cognitiva e mortalidade após a alta hospitalar em pacientes idosos com insuficiência cardíaca avançada

Abstract: 64 anos (68 ±7) e fração de ejeção < 0,45 (0,38 ± 0,06). Submetidos a testes cognitivos (digit span, digit symbol, letter cancellation, trail making A e B) e teste de caminhada de 6min, 4 dias antes da alta (T1) e 6 semanas após (T2), cujos desempenhos foram comparados pelo teste T. O valor prognóstico dos escores dos testes cognitivos foram analisados pela regressão logística e o valor de maior acurácia dos testes associado com o prognóstico determinado pela ROC curve. RESULTADOS: Após 24,7 meses, 17 (55%) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…The sample included patients with HF of both sexes, with a higher prevalence of male, married and Caucasian individuals. The characteristics found are similar to those previously described by other authors 8,14,[18][19][20][21][22][23]32 .…”
Section: Sociodemographic and Assistential Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…The sample included patients with HF of both sexes, with a higher prevalence of male, married and Caucasian individuals. The characteristics found are similar to those previously described by other authors 8,14,[18][19][20][21][22][23]32 .…”
Section: Sociodemographic and Assistential Characteristicssupporting
confidence: 91%
“…The mean age was 54.25 ±11.82 years in the IG and 60.65±7.03 years in the CG, which characterized a relatively young sample when compared to other studies, in which the mean age was higher 8,10,14,15,18,[20][21][22] .…”
Section: Sociodemographic and Assistential Characteristicscontrasting
confidence: 52%
“…Decompensated heart failure in the elderly is characterized by more diastolic dysfunction, more worsening renal function,15 worse cognitive function,16 and a worse prognosis. Our results are compatible with those of the ADHERE study, which found younger age and ejection fraction in patients who required inotropic therapy 2.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated important cognitive impairment in elderly patients with advanced heart failure. 20 A moderate to severe cognitive decline was also observed in 70% of the patients aged ≥ 55 years undergoing HD. 21 At the Digits test, there was a statistical difference (p = 0.03) and the patients undergoing PD presented the worst performance.…”
Section: Discussionmentioning
confidence: 95%